FENOMENA TREND CADAR PADA MAHASISWA UIN SUSKA RIAU - Lisa Afista; Yoserizal " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
The research was carried out at the UIN SUSKA Riau campus, Km. 15 Jl. H.R Soebrantas, Simpangbaru, Tampan, Pekanbaru. The purpose of this study was to determine the factors causing niqab / veil trends in students UIN SUSKA Riau and the response around the students UIN SUSKA Riau to the trend of using the niqab / veil on campus UIN SUSKA Riau. The focus of this research is to find out the factors that cause the niqab / veil trend at UIN SUSKA Riau. Informants in this study were 6 people. The writer uses qualitative methods and uses purposive sampling technique. Data instruments are observation, interview, and documentation. From research conducted by the author, the writer found that what caused the trend of wearing niqab / veil at UIN SUSKA Riau was because they wore the veil that emerged from their own desires. Before they want to wear the veil they seek knowledge about the veil in various studies, both those on campus, off campus, or social media. There are also those who have known the veil law since at the pesantren. Besides that, the environment at UIN SUSKA Riau also supports the use of the veil because there is no prohibition on the use of the veil and students, lecturers, and employees of UIN SUSKA Riau do not mind this.Keywords: Veil, UIN SUSKA Riau, Trend